Former Students’ Perceptions Toward RSBI Program: A Reflection of Indonesia’s Abolished Bilingual Program - Putu Yoga Sathya Pratama; Luh Putu Artini; Ni Putu Era Marsakawati (Graduate School of Universitas Negeri Malang, 2023)
This article is an attempt to describe RSBI program’s reflection from the former students’ perceptions. The article employed case study research design to explore students’ perceptions with particular emphasis on the use of bilingualism in the classroom. The data were gathered from interview toward 17 former students of RSBI program. The obtained data were analyzed qualitatively and inductively. Results presented RSBI program were perceived diversely from the reason, experience, and expectation viewpoints. Implications portrayed evaluation material in planning future programs that intensify the implementation of international-standards in general, or the use of two languages in the classroom in particular.